Caracterização bioquímica e funcional de um inibidor de Fosfolipase A2 do tipo γ isolado do soro de Crotalus durissus collilineatus - Gimenes, Sarah Natalie Cirilo (2013)
Some animals have a natural resistance to toxic effects induced by snake venom due to presence of natural endogenous inhibitors in their plasma. Snake venom contains inhibitors of phospholipase A2 (PLA2) that inhibit the enzymatic and pharmacological activities of PLA2. In this work we show the isolation, structural and biochemical characterization of a new PLA2 inhibitor from Crotalus durissus colillineatus (Cdc) snake serum by two chromatographic steps. Initially, the Cdc serum was applied to a column of ion exchange Q-Sepharose Fast Flow, producing six peaks of absorbance at A280nm (Q1 to Q6). Subsequently, Q4 fraction (best results to inhibition) was applied to affinity chromatography with immobilized HiTrap NHS-BnSP-7. This fractionation resulted in two fractions (NHS-1 and NHS-2) the second fraction contained the inhibitor, named γCdcPLI. The molecular mass of γCdcPLI determined by MALDI-TOF was 22.3kDa and the primary partial structure obtained by Edman and peptide mass fingerprinting (PMF) MS (MALDI-TOF \\ TOF), showed similarity when compared with the sequences of other related inhibitors. The secondary structure was evaluated for circular dichroism and showed approximately 22% alpha helix and 29% beta sheets.These studies of interaction have also indicated no significant changes in secondary structure to γCdcPLI and BnSP-7. The results obtained by analysis of dynamic light scattering (DLS) showed that the inhibitor has in oligomerization variation, according to temperature and when dissolved in H2O or PBS. γCdcPLI was able to inhibit the enzymatic, with 100% to inhibition. Cytotoxicity was assayed on Murine endothelial cell line derived from thymus hemangioma- tEnd to MTT and myotoxicity was measuring by creatine kinase (CK) showed inhibition too, but in this case the inhibition was independent dose. Structural and functional studies of this inhibitor may contribute to understanding the mechanisms of action of PLA2 inhibitors. In addition, these studies may serve as starting point for investigating the potential of these inhibitors for the treatment of snake bite or inflammatory diseases.